Green accounting, pengungkapan sustainability reporting dan CSR terhadap nilai perusahaan - Elsa Nurani Safitri, Neng; Widiyati, Dian (Jurnal Riset Pendidikan Ekonomi, 2025)
This research aims to examine the influence of Green Accounting, sustainability reporting disclosure, and Corporate Social Responsibility on firm value. This study uses Green Accounting, sustainability reporting disclosure, and Corporate Social Responsibility as independent variables. The population in this study consists of companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The total population in the basic materials sector is 106 companies. From this population, a purposive sampling technique was used with specific criteria to determine the sample, resulting in a sample of 12 companies with 36 observational data points. The data analysis technique used in this research involves Eviews 12, which includes descriptive statistical tests, panel data model analysis, classical assumption tests, and hypothesis testing. The results of these tests demonstrate that Green Accounting, sustainability reporting disclosure, and Corporate Social Responsibility simultaneously affect firm value. However, partially, Green Accounting and Corporate Social Responsibility do not have a significant impact on firm value, whereas sustainability reporting disclosure does influence firm value.